Synthesis and Antibacterial Activity of 3-Phenyl-4-Styryl Coumarins - M. Barot, Vijay (Asian Journal of Chemistry, 2010)
Several related 3-phenyl-4cstyryl coumarins are prepared with a view to the fact that a number of related compounds are known to possess biological activity.